Effect of Interface Modified by Graphene on the Mechanical and Frictional Properties of Carbon/Graphene/Carbon Composites - Yang, Wei (Materials (Basel), 2016)
In this work, we developed an interface modified by graphene to simultaneously improve the mechanical and frictional properties of carbon/graphene/carbon (C/G/C) composite. Results indicated that the C/G/C composite exhibits remarkably improved interfacial bonding mode, static and dynamic mechanical performance, thermal conductivity, and frictional properties in comparison with those of the C/C composite. The weight contents of carbon fibers, graphene and pyrolytic carbon are 31.6, 0.3 and 68.1 wt %, respectively. The matrix of the C/G/C composite was mainly composed of rough laminar (RL) pyrocarbon. The average hardness by nanoindentation of the C/G/C and C/C composite matrices were 0.473 and 0.751 GPa, respectively. The flexural strength (three point bending), interlaminar shear strength (ILSS), interfacial debonding strength (IDS), internal friction and storage modulus of the C/C composite were 106, 10.3, 7.6, 0.038 and 12.7 GPa, respectively. Those properties of the C/G/C composite increased by 76.4%, 44.6%, 168.4% and 22.8%, respectively, and their internal friction decreased by 42.1% in comparison with those of the C/C composite. Owing to the lower hardness of the matrix, improved fiber/matrix interface bonding strength, and self-lubricating properties of graphene, a complete friction film was easily formed on the friction surface of the modified composite. Compared with the C/C composite, the C/G/C composite exhibited stable friction coefficients and lower wear losses at simulating air-plane normal landing (NL) and rejected take-off (RTO). The method appears to be a competitive approach to improve the mechanical and frictional properties of C/C composites simultaneously.